A cross-sectional study on elevated levels of serum amylase as a predictive factor for appendiceal perforation in patients with acute appendicitis - Patra, Sidhartha; Das, Deepak Kumar; Sarkar, Anup Kumar; Jenamani, Abhisek; Barik, Surya Narayan; Acharya, Ashoak (International Journal of Research in Medical Sciences, 2025)
Background: Acute appendicitis is a common surgical emergency, and appendiceal perforation can lead to serious complications. Early identification of perforation is critical to improving outcomes. Serum amylase has been suggested as a potential marker for perforated appendicitis, but its diagnostic accuracy remains under-investigated. This study aimed to evaluate the diagnostic utility of elevated serum amylase levels as a predictive factor for appendiceal perforation in patients with acute appendicitis. Methods: An observational study was conducted at Hi-tech medical college and hospital, Bhubaneswar, from December 2023 to February 2025. Sixty-four patients diagnosed with acute appendicitis and undergoing appendectomy were included. Preoperative serum levels of amylase and lipase were measured. Postoperative histopathological examination confirmed the diagnosis of perforated or non-perforated appendicitis. Statistical analysis was performed using chi-square test, t-test, and ROC curve. Results: Among the 64 patients, 28 had perforated appendicitis, and 36 had non-perforated appendicitis. The mean serum amylase level was significantly higher in the perforated group (72.1±27.3 mg/dl) compared to the non-perforated group (30.1±11 mg/dl) (p<0.0001). No significant difference was observed between groups regarding serum lipase. Conclusions: Elevated serum amylase levels were associated with perforated appendicitis in patients with acute appendicitis. Serum amylase demonstrated high diagnostic accuracy and could serve as a predictive marker for appendiceal perforation. Further studies are warranted to validate these findings and explore the clinical utility of serum amylase in the early diagnosis of perforated appendicitis.